Hubungan Gaya Hidup terhadap Kasus Penyakit Infeksi Saluran Kemih (ISK) pada Wanita di Puskesmas Oebobo Kota Kupang Tahun 2022 - Lucitania Floreca Mokos; Indriati A. Tedju Hinga; Soleman Landi (Yayasan Literasi Sains Indonesia, 2023)
The Oebobo Health Center in Kupang City is the health center that has the most UTI cases in women in 2021 with 38 cases compared to men with 27 cases. Urinary Tract Infection (UTI) is a disease that is prone to occur in women, not only the elderly, but teenagers are also susceptible to UTI. The problem is a bad lifestyle such as the habit of holding back urination (BAK), not consuming enough water, the habit of changing underwear and pads, cleaning the intimate organs after urinating and defecating can trigger UTIs. This study aims to analyze the relationship between lifestyle and cases of Urinary Tract Infection (UTI) in women at the Oebobo Health Center in Kupang City in 2022. The type of research conducted was an analytic survey with a case control design. The sample consisted of 36 case samples selected using total sampling and 36 control samples selected using simple random sampling with a significance level of Î±=0.05. Data analysis used in this study was univariate and bivariate analysis using the chi square statistical test. Each of the variables studied was tested using the chi square statistical test to determine the relationship with UTI disease variables. The results of this study indicate that there is a relationship between consuming water (p-value=0.0009, OR=17.286), holding urination (p-value=0.001, OR=6.250), changing pads (p-value=0.009, OR=4.086)) with UTI, while the habit of cleaning intimate organs after urinating and defecating (p-value=0.429), changing underwear (p-value=0.674) has no relationship with UTI. Suggestions for UTI sufferers and the public, especially women, to maintain a healthy lifestyle by reducing bad habits that trigger UTIs.